Pengaruh Kompetensi Pedagogik Dan Kompetensi Profesional Guru Terhadap Motivasi Belajar Peserta Didik Di SMA Negeri 2 Banjar - Purwanti, Sri Dian (STAI Denpasar Bali, 2023)
The research background is the low learning motivation of students at SMA Negeri 2 Banjar and is influenced by pedagogic competence and teacher professional competence. The aims of this study were to: 1) The influence of teacher pedagogic competence on the learning motivation of students at SMA Negeri 2 Banjar. 2) The effect of teacher professional competence on students' learning motivation at SMA Negeri 2 Banjar. 3) The effect of teacher pedagogic competence and teacher professionalism on students' learning motivation at SMA Negeri 2 Banjar. The research method used is descriptive method with a quantitative approach. The data collection technique was carried out by distributing questionnaires with a total of 56 respondents. Statistical data processing using SPSS 21.0. The results of the study show that 1) Teacher Pedagogic Competence at SMA Negeri 2 Banjar in general is in the frequent answers with quite high criteria, however there are indicators that need to be improved, namely training teachers specifically and personally. The results of testing the relationship between teacher pedagogic competence and student learning motivation are included in the moderate correlation category, then there is a positive influence of teacher pedagogic competence on student learning motivation. 2) The professional competence of teachers in SMA Negeri 2 Banjar in general is in the professional answers of teachers in SMA Negeri 2 Banjar which is in the answer often with moderate criteria, however there are indicators that must be improved, namely increasing teacher professionalism from various sources. The results of the hypothesis test show that the teacher's professional competence has an effect of 35.1% on students' learning motivation while 64.9% is affected by other factors. Thus the professional competence of teachers has a positive effect on students' learning motivation. 3) The learning motivation of students is generally at a fairly high criterion. However, there are indicators that need to be improved, namely the development of self-students to foster a sense of enthusiasm for success.